O jo, nu'ca menibat? (ca-2ng pamiapag) : suglung at iamut deng piling amanung Capampangan - Osmubal Papa (Oscar M. Balajadia); Tantingco, Robby P. (Robert P. Tantingco) ([Angeles City] Juan D. Nepomuceno Center for Kapampangan Studies, Holy Angel University, 2012)
On the etymology of Kapampangan words and phrases.
"Caduang pami-apag."--Cover.
In Pampanga.
Keywords: Pampanga language -- Etymology; Pampanga language -- Glossaries, vocabularies, etc